Chemistry for kids : homemade science experiments and activities inspired by awesome chemists, past and present - Heinecke, Liz Lee (Quarry Books, an imprint of The Quarto Group, 2020)
Provides brief biographies of twenty-five diverse chemists past and present, explains the importance of their work, and pairs each profile with a chemistry experiment or hands-on activity designed for kids. Features full-color illustrations and photographs, step-by-step instructions, a glossary, the periodic table, and further resources.